Apicoplast-Resident Processes: Exploiting the Chink in the Armour of Plasmodium falciparum Parasites - Collins Ojonugwa Mamudu; Mercy Eyitomi Tebamifor; Mary Ohunene Sule; Titilope Modupe Dokunmu; Olubanke Olujoke Ogunlana; Franklyn Nonso Iheagwam (Hindawi Limited, 2024)
The discovery of a relict plastid, also known as an apicoplast (apicomplexan plastid), that houses housekeeping processes and metabolic pathways critical to Plasmodium parasites' survival has prompted increased research on identifying potent inhibitors that can impinge on apicoplast-localised processes. The apicoplast is absent in humans, yet it is proposed to originate from the eukaryote's secondary endosymbiosis of a primary symbiont. This symbiotic relationship provides a favourable microenvironment for metabolic processes such as haem biosynthesis, Fe-S cluster synthesis, isoprenoid biosynthesis, fatty acid synthesis, and housekeeping processes such as DNA replication, transcription, and translation, distinct from analogous mammalian processes. Recent advancements in comprehending the biology of the apicoplast reveal it as a vulnerable organelle for malaria parasites, offering numerous potential targets for effective antimalarial therapies. We provide an overview of the metabolic processes occurring in the apicoplast and discuss the organelle as a viable antimalarial target in light of current advances in drug discovery. We further highlighted the relevance of these metabolic processes to Plasmodium falciparum during the different stages of the lifecycle.